Production of cloned intra- and interspecies caprine embryos through somatic cell nuclear transfer technique with special reference to donor karyoplast type and recipient cytoplast source / Asdiana Amri - Asdiana, Amri (2015)

(untitled)
In Malaysia, low goat population and high demand for such products from goat meat, milk and manure contribute to increase goat production to ensure food security and to improve the strategic and socio-economic status of the citizen, especially the rural population and also possibly for the commercialisation of goats. Therefore, using advanced assisted reproductive techniques (ART) through intra- and interspecies somatic cell nuclear transfer (SCNT) in order to produce cloned caprine embryos and subsequently offspring for propagation of genetically improved goat population at a rapid rate. The main objective of this research was to produce in vitro cloned caprine embryos through SCNT with special reference to recipient cytoplast source and donor karyoplast type. Briefly, caprine oocytes were obtained from two different oocyte sources (laparoscopic oocyte pick-up and abattoir), meanwhile bovine oocytes were only obtained from abattoir-derived oocytes. The collected oocytes were cultured in in vitro maturation medium (IVM) in CO2 incubator (5%) at 38.5oC for 21 to 24 hours (LOPU-derived oocyte) and 24 to 27 hours (abattoirderived oocyte) for maturation. After maturation, cumulus oocyte complexes (COC) were removed by denuding in hyaluronidase (0.2%). The matured oocyte was confirmed by the extrusion of the first polar body (PB1) and enucleated by using laser technique followed by injection of the donor karyoplast (fresh cumulus cell or ear fibroblast cell) into the successful enucleated oocyte using whole-cell intracytoplasmic injection (WCICI) technique. The successful reconstructed oocytes were activated by using combination of calcium ionophore (CaI) for 5 minutes followed by 6-dimethylaminopurine (6-DMAP) for 4 hours which then were cultured in KSOM medium in CO2 incubator (5%) at 38.5oC for further development. Observation of the cleavage of reconstructed embryo was carried out daily. ii In Experiment 1, evaluation of the effect of oocyte sources on quantity and quality of oocytes obtained, maturation rate as well as subsequent in vitro culture performance of SCNT embryos were performed. There were no significant differences in the percentages of oocyte quality in LOPU versus abattoir: Grade B (36.24±2.6 vs. 33.23±2.7, respectively) and C (24.56±3.3 vs. 28.11±2.9, respectively); however, significant differences were shown in Grade A (32.46±4.4 vs. 19.80±4.4, respectively) and Grade D (6.74±1.7 vs. 18.86±2.0, respectively). Oocytes retrieved from LOPU showed the highest maturation rate was obatained from Grade A (77.62±6.7%) followed by Grade B (76.63±4.3%), Grade C (39.64±7.8%) and Grade D (21.97±8.5%), whereby Grades A and B were significantly higher than Grades C and D (P<0.05). Meanwhile in oocytes retrieved from abattoir showed no significant differences in maturation rates among the groups: Grades A (46.94±7.7%), C (63.80±7.8%) and D (58.24±7.4%), however, Grade C oocytes were significantly higher than those of Grade B (39.54±5.6%). When comparing the 2 oocyte-sources according to respective grade of oocytes, LOPU-derived oocytes was significantly higher (P<0.05) than abattoir-derived oocytes on the maturation rate in good quality of oocytes of Grades A and B. In in vitro developmental of embryo after SCNT, there were significant differences in cleavage rate of cloned embryos in LOPU versus abattoir: 2-cell (86.84±7.0 vs. 41.04±11.3%, respectively), 4-cell (84.03±8.5 vs. 35.06±10.8%, respectively), 8-cell (71.12±6.8 vs. 24.30±9.9%, respectively) and morula (47.59±7.2 vs. 16.48±7.2%, respectively). In Experiment 2, the effect of time interval (36 to 40 hours; 66 to 70 hours; 71 to 75 hours) from PMSG/ hCG injection to LOPU on caprine stimulation response, oocyte recovery and maturation rate were investigated. These 3 different time intervals had significant differences in number of stimulated follicles and number of oocytes recovered. iii However, there was no significant difference in number of ovulated follicles (presence of corpus luteum). The recovered oocytes were randomly cultured in IVM medium for the maturation process. During IVM, time interval of 66 to 70 hours gave the highest survival rate (95.07±2.3%) followed by time interval of 71 to 75 hours (92.29±2.3%) and 36 to 40 hours (78.73±4.1%), which correspondingly to the maturation rate (75.64±3.4, 65.30±3.6 and 53.92±2.1%, respectively). In Experiment 3, the effect of different types of donor karyoplast on the cleavage rate of cloned caprine embryos after SCNT was conducted. There was no significant difference in the enucleation rate and injection rate of two different types of fresh cumulus cell versus ear fibroblast cell (97.61±2.4 vs. 100.00% and 95.15±3.4 vs. 94.32±4.0%, respectively). The cleavage rate of cloned caprine embryo using ear fibroblast cell as donor karyoplast were significantly higher than the cumulus cell (82.76±5.1 vs. 57.17±5.6%, 75.97±7.5 vs. 46.38±7.1%, 64.49±9.8 vs. 27.25±8.7% and 50.82±10.4 vs 15.59±7.0%, respectively). In Experiment 4, the efficacy of two different SCNT approaches, namely intraspecies SCNT and interspecies SCNT on the cleavage rate of cloned caprine embryos, and attempts of transferring of cloned embryo into surrogate mother were conducted. There were no significant differences between intra- and interspecies in respective maturation rate (66.08±3.8 and 59.68±4.9%, respectively), enucleation rate (98.90±1.1 and 96.95±2.3%, respectively) and injection rate (94.70±2.6 and 100%, respectively). The cleavage rates of intraspecies cloned embryos were significantly higher (P<0.05) than those of interspecies in all cases of preimplantation developmental stage: 2 cell (75.67±3.7 vs. 55.06±4.1%), 4 cell (64.86±5.4 vs. 48.58±4.5%), 8 cell (53.14±5.7 vs. 34.21±5.3%) iv and morula (38.55±5.1 vs. 23.24±3.9%). A total of 29 cloned embryos from the both SCNT approaches were transferred into the uterine horn of 8 recipient does. Unfortunately, no pregnancy was detected. In conclusion, due to low population of goat in Malaysia, the difficulties in supply of caprine oocytes, the production of in vitro caprine embryos through assisted reproduction technique such as IVF, ICSI and SCNT was limited. Therefore, to choose recipient cytoplast source and donor karyoplast type was very important to maximise the efficacy in production of cloned caprine embryos and subsequent live offspring. Beside, the interspecies SCNT approach by using different species of recipient cytoplast (bovine oocyte) will be an alternative for the production of cloned caprine embryos in future which could be transferred into surrogate mother to develop full-term.